Temporal and spatial host abundance and prevalence of Andes hantavirus in southern Argentina - Polop, Francisco J (2010)
Fil: Polop, Francisco J. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET), Buenos Aires; Argentina.